DESIGN AND DEVELOPMENT OF AN AUTOMATIC AND MAINTENANCE-FREE EBB AND FLOW HYDROPONICS SYSTEM - Ramos, Berlin (International Journal of Arts, Sciences and Education, 2021)
This study developed and designed an automatic and maintenance-free Ebb and Flow Hydroponics System. It also assessed the quality of the developed hydroponics system through the use of ISO 25010 Software Product Quality Standards. Five (5) IT experts were utilized to determine the quality of the developed Ebb and Flow Hydroponics System, whereas, they assessed the device in terms of functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. Similarly, twenty (20) end-users specifically fifteen (15) agriculture students and five (5) agriculture teachers, assessed the were functional suitability, usability, and portability of the device. The study made use of Robotic Process Automation (RPA) which is the method that highlights construction, development, and improvement of thee product. RPA also have an emphasis on discovery, analysis, design, implementation, and support. In terms of the IT experts’ assessment on the developed Hydroponics System, the study revealed that the overall mean rating of IT experts in terms of the entire ISO 25010 quality standards was equivalent to excellent. This means that IT experts recognized at least 2 evidences on the existence of the quality with no error / revision in all its characteristics. In addition, as assessed by the end-users, the functional suitability of the developed hydroponics system was very good. This means that the end-users recognized at least 2 evidences on the existence of the functional suitability of the device but with 1 minor revision. Nonetheless, usability and portability as assessed by the end-users were both excellent. This clearly shows that the device could be easily used even by new users, can easily be installed in any android phone, and parts of the device can easily be replaced to to the availability of its parts in the market. The researcher therefore recommended to schools with limited land area to use Automatic and Maintenance-Free Ebb and Flow Hydroponics System to expose their students in planting crops. It was also recommended for other researchers to develop a system that can detect acidity levels of pH solution, viscosity, oxygen, and other aspects, as well as to develop a wider scale system since the researcher only developed a small scale hydroponic system. Enhancement in security features is also recommended. Moreover, since the school where the study was conducted was very prone to burglars, anti-theft alarm should also be incorporated in the device to prevent theft of the developed hydroponic system.